Mechanical properties and damping characteristics of Egyptian granite-epoxy composite material - Yasser Abdelrhman; Mohamed Omar; Ibrahim M Hassab-Allah; W M Shewakh; Wael M Khierldeen; Mohammed Hedaya; Refaie Omar; Mohamed F Younes (Materials Research Express, 2024)
Vibrations generated during the operations of machine tools, especially at high-speed operation impact several issues in machined parts such as imprecision dimensions and a poor surface finish. This prompts research and studies into alternative materials for machine tool structures to provide considerable damping performance and acceptable stiffness compared to traditional materials. This paper deals with the experimental study of a developed granite-epoxy composite, made from waste granite and local epoxy as an alternative material for machine tool structures. A waste of Egyptian Red Aswan granite was used as filler after being crushed and sifted into three sizes: fine (less than 1 mm), medium (1 to 5 mm), and coarse (5 to 8 mm). A local commercial epoxy resin kemapoxy 150 was added to a granite aggregate mixture having grain proportions 50:25:25 for fine, medium, and large, respectively. The influence of the variation of the epoxy weight ratio on the static and damping characteristics of a proposed granite–epoxy composite material was experimentally investigated. To ensure a coherent granite-epoxy composite, the required minimum resin content of 13.88 wt% was determined, and the granite/epoxy ratios were selected as 85:15 wt%, 80:20 wt%, and 75:25 wt%. The findings exhibit that the largest compressive strength of 76.8 MPa and the greatest flexural strength of 35.4 MPa is achieved at the highest epoxy weight ratio of 25%. The largest damping ratio of 0.0202 is observed at the epoxy ratio of 20% and it decreases to 0.015 when the epoxy ratio is increased to 25%. An Egyptian granite-epoxy composite, made from waste granite and local epoxy, is a promising alternative material for machine tool structures. It offers both economic and environmental benefits, along with high mechanical and damping properties compared to traditional machine tool materials.